The development of biodegradable superabsorbent polymer hydrogel from sago starch - Nurizan binti Omar (Kulliyyah of Engineering, International Islamic University Malaysia, 2015)
Last several decades, many researches have been conducted to replace the synthetics superabsorbent polymer hydrogels (SAPH) by the greener alternatives since it has been reported that serious environmental pollution was created by synthetic polymers especially in most developing country. It is generally known that ordinary synthetic superabsorbent polymer hydrogels had occupied in industry especially in personal care industry because it is relatively low cost, uncomplicated processing technique as well as superior water absorbency property. Even so, the concern is therefore lies in the creation of environmental friendly with higher performance type natural based superabsorbent polymer hydrogels. The efforts currently under way in producing natural superabsorbent polymer hydrogels with use of natural polysaccharide, sago starch in turn to reduce the use of synthetic monomers such as polyacrylic acid (PAA), polyacrylonitrile (PAN) and acrylamide (AM) which at the same time provide hydrogels with better properties. The effects of crosslinker, methylenebisacrylamide (MBA) content, initiator, ammonium peroxydisulphate (APS) and sago starch to monomer, polyacrylic acid (PAA) on the properties of sago starch superabsorbent hydrogel (SSPH) were studied. In this work SSPHs were produced via graft copolymerization process of PAA onto sago starch in the presence of APS and MBA as initiator and crosslinker respectively. The starch gelatinization temperature and processing temperature were fixed at 80°C and 40 °C respectively. This current work was divided into three parts in order to achieve SSPH with greatest percentage grafting efficiency (%GE) and percentage water absorbency (%WA). The formation of crosslinked network of hygrogels was confirmed trough FTIR analysis and the thermal stability of SSPHs was studied in each part of investigation. For the first part, the amount of MBA was varied from 0 to 4 wt% based on the weight of monomer. Here, the maximum percentage water absorbency (%WA) of 45.1% was attained at SSPH with 1 wt% MBA and the highest %GE of 38.57% also obtained at SSPH with 1 wt% MBA. For the second part the %GE of SSPHs was increased with increasing amount of APS up to 3 wt% based on weight of monomer and then decrease. The maximum %GE of 39.5% was recorded at SSPH with 3wt % APS. The maximum %WA of 48.78% was recorded at SSPH with 3 wt% APS. For the third part of investigation, the focus lies on the effects of starch to monomer ratios to the properties of SSPH. Since the optimum amount of MBA crosslinker and APS initiator had obtained in the previous first part and second part, for the third part of investigation, the amount of MBA and APS was fixed at 1 wt% and 3 wt% correspondingly. In this part, the ratios of starch to monomer were varied from 1.0:2.0 to 2.5:20. For the %GE, the highest %GE of 52.58% was obtained at starch to monomer ratio of 1.5:2.0. When increasing the sago starch content, the %GE decreased gradually. The SSPH with highest %GE also resulted in highest %WA. Maximum %WA of 68% was recorded at SSPH with starch to monomer ratio 1.5:2.0. In the soil biodegradation study, the result confirmed that SSPH has higher percentage degradation than synthetic SAPH. The percentage degradation for SSPH in 60 days was recorded at 74.7 % while for synthetic SAPH was recorded at 31 %. On the basis of the results, this is a good illustration of approach towards competent exploitation of natural resources to produce biodegradable superabsorbent polymer hydrogels.